Building ETL Pipelines with Python : Create and deploy enterprise-ready ETL pipelines by employing modern methods /: Create and deploy enterprise-ready ETL pipelines by employing modern methods. (2023) - Pandey, Brij Kishore; Schoof, Emily Ro
No abstract available